Bolton freeware: aplicativo de avaliação de discrepância de massa dentária desenvolvido pelo programa de pós-graduação em odontologia/UFRN - Farias, Arthur Costa Rodrigues (2013)
The calculation of tooth mass discrepancy, essential for good planning and a proper orthodontic finishing, when performed manually, besides being laborious, requires considerable time consumption. The aim of this study was to develop and test Bolton Freeware, a software for analysis of the tooth mass discrepancy of Bolton, aiming to minimize the consumption of time in a less onerous way. The digital analysis of the software was done by means of two-dimensional scanning of plaster study models and compared to manual evaluation (gold standard), using 75 pairs of stone plaster study models divided into two groups according to the magnitude of the Curve of Spee (group I from 0 to 2 mm, group II greater than 2 to 3mm). All the models had permanent dentition and were in perfect condition. The manual evaluation was performed with a digital caliper and a calculator, and the time required to perform the analysis for both methods was recorded and compared. In addition, the software was evaluated by orthodontists regarding its use, by means of questionnaires developed specifically for this purpose. Calibration was performed prior to manual analysis, and excellent levels of inter-rater agreement were achieved, with ICC > 0.75 and r > 0.9 for total and anterior proportion. It was observed in the evaluation of error of the digital method that some teeth showed a significant systematic error, being the highest measured at 0.08 mm. The analysis of total tooth mass discrepancy performed by Bolton Freeware, for those cases in which the curve of Spee is mild and moderate, differ from manual analysis, on average, 0.09 mm and 0.07 mm respectively, for each tooth evaluated, with r> 0, 8 for total and anterior proportion. According to the specificity and sensitivity test, Bolton Freeware has an improved ability to detect true negatives, i.e. the presence of discrepancy. The Bolton analysis digitally performed was faster, with an average difference of time consumed to perform the analysis of Bolton between the two methods of approximately 6 minutes. Most experts interviewed (93%) approved the usability of the software